Enhancing Student Engagement and Academic Performance through Gamification-Based Learning in Elementary Mathematics Education - Sitepu, Ediaman; Natasya, Laura Myrolind; Sitopu, Joni Wilson; Mardiati, Mardiati; Charolina, Tiara (Institute of Computer Science (IOCS), 2024)
This research investigates the implementation of gamification-based learning in mathematics education at the elementary school level, aiming to enhance student engagement, academic performance, and teacher perceptions. Utilizing a mixed-methods approach, the study involved quantitative data from standardized assessments and surveys, alongside qualitative insights from interviews and classroom observations. Results indicated a significant increase in student engagement, with 85% of participants reporting heightened interest in mathematics following the introduction of gamified activities. Academic performance improved, with an average increase of 15% in mathematics scores, corroborating findings from prior research that links gamification to enhanced learning outcomes. Teachers reported positive perceptions of gamification, noting increased student motivation and improved classroom dynamics, although challenges related to task complexity and time investment for implementation were also identified. This research contributes to the growing body of literature on gamification in education, highlighting its potential to create dynamic and interactive learning environments while emphasizing the need for adequate support and professional development for educators. The findings suggest that when implemented thoughtfully, gamification can significantly transform mathematics teaching, fostering critical thinking and collaboration, and ultimately inspiring a lifelong appreciation for the subject among elementary students.